Patient Perceptions of the Implementation of the Universal Health Coverage Program in Health Services at Jajaway Community Health Center - Sali Setiatin; Asep Ma'mun Sanusi (International Journal of Health Sciences, 2026)
Universal Health Coverage is a government effort to ensure fair, quality, and affordable health services for all citizens. Community Health Centers (Puskesmas), as first-level health facilities, play a crucial role in the successful implementation of the program. Studies integrating patient experiences and perceptions into primary-level implementation remain limited, with most focusing on enrollment coverage and administrative aspects. This study aimed to understand patient perceptions of UHC implementation at the Jajaway Community Health Center in Bandung City. This study employed a descriptive qualitative approach. The informants consisted of UHC patients. Data were collected through in-depth interviews and observations, then analyzed thematically using a structure-process-outcome framework. The results showed that UHC implementation has generally been effective in improving access to health services and alleviating financial burdens, as reflected in patients' positive perceptions. In the process dimension, the role of staff in interpersonal communication and the empathetic attitude of health workers were dominant factors in shaping these perceptions. Challenges were found in the form of patients' limited understanding of service mechanisms and limited access to information. An in-depth understanding of patient perceptions of UHC implementation is an important factor in assessing the success of UHC implementation.